Mucuna pruriens grain meal, germinated and non- germinated, for broilers: their effect on physiological indicators - Martínez, Madeleidy; Díaz, María Felicia; Hernández, Yasmila; Sarmiento, Mariela; Sarduy, Lucia; Sierra, F. (Cuban Journal of Agricultural Science, 2016)
In order to evaluate the replacement of soybean by Mucuna pruriens (mucuna) grain meal, germinated and non- germinated, in physiological indicators of broilers, a total of 30 male broilers of 21 d of age were used, distributed according to completely randomized design with three treatments. These consisted of an equal number of experimental diets for grower and finisher,respectively: control (maize-soybean paste) and the inclusion of soybean paste by 10% of grain meal of the raw and germinated legume of the ration. Caecal, health and morphometric indicators of the gastrointestinal tract (GIT) were studied. To the latter, Pearson correlation was performed and, later, multivariate analysis using the principal components method. There was a correlationbetween the 27 variables studied in the morphometric indicators.The production of total short chain fatty acids (SCFA) in cecum was lower with the inclusion of grain meal of the non-germinated legume compared with the rest of treatments that did not differ between each other (176.44 vs 208.30 and 211.20 meq/L). Nodifferences were observed for the immunological organs, blood indicators and main components of carcass and live weight. It is concluded that when supplying diets to birds with mucuna grains, germinated and non-germinating, the GIT weight was modified to make a more efficient use of the food and did not affect the health or the body composition of the broiler which intake the diet.Key words: legume, germination, physiology, birds